Iodinated Bis(phthalocyaninato)terbium(III) Complexes: Versatile Platforms for Functionalization of Single‐Molecule Magnets through Sonogashira Reaction. Issue 32 (1st October 2015) - Bertani, Federico; Cristiani, Nicola; Mannini, Matteo; Pinalli, Roberta; Sessoli, Roberta; Dalcanale, Enrico
Abstract: Novel homoleptic octaiodinated bis(phthalocyaninato)terbium(III) complex Tb(PcI4 )2 (1 ) and its heteroleptic counterpart tetraiodinated TbPc(PcI4 ) have been synthesized in their neutral forms and fully characterized. Their magnetic properties have been evaluated by standard magnetometry, and the results confirm the single‐molecule magnet behavior of these two complexes. The eight aryl iodine moieties in the homoleptic derivative1 have been exploited to test the Sonogashira reaction with 4‐pentyn‐1‐ol as alkynyl substrate at room temperature under standard conditions. The application of this new synthetic protocol for TbPc2 functionalization to different substrates will allow the introduction of a wide range of functionalities on LnPc2, which is a necessary prerequisite for the development of SMM‐based technologies. Abstract : Iodinated TbPc2 have been synthesized and their single‐molecule magnetic behavior has been studied by measuring their magnetic susceptibility. Incorporation of iodine in the molecular structure of the complex has allowed further functionalization through Sonogashira reaction. In this way, a wide range of LnPc2 derivatives bearing different functionalities can be easily obtained.